2018
DOI: 10.1186/s12864-018-5282-9
|View full text |Cite
|
Sign up to set email alerts
|

A context-free encoding scheme of protein sequences for predicting antigenicity of diverse influenza A viruses

Abstract: BackgroundThe evolution of influenza A viruses leads to the antigenic changes. Serological diagnosis of the antigenicity is usually labor-intensive, time-consuming and not suitable for early-stage detection. Computational prediction of the antigenic relationship between emerging and old strains of influenza viruses using viral sequences can facilitate large-scale antigenic characterization, especially for those viruses requiring high biosafety facilities, such as H5 and H7 influenza A viruses. However, most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Herein, we improved our proposed method in [21] so that the encoding scheme can be applied to both protein sequences with varying lengths and protein sequence pairs, which covers the most situation of sequence analyses in bioinformatics. The method, CFreeEnS, is based on the AAindex database [22], which is the collection of amino acid indexes and mutation matrices from published work, representing physiochemic and biochemical properties related to the specificity and diversity of protein structures and functions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Herein, we improved our proposed method in [21] so that the encoding scheme can be applied to both protein sequences with varying lengths and protein sequence pairs, which covers the most situation of sequence analyses in bioinformatics. The method, CFreeEnS, is based on the AAindex database [22], which is the collection of amino acid indexes and mutation matrices from published work, representing physiochemic and biochemical properties related to the specificity and diversity of protein structures and functions.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work has demonstrated that CFreeEnS is effective in predicting the antigenic similarity between the hemagglutinin protein of influenza viral strains [21], indicating that CFreeEnS for protein sequence pairs can distinguish subtle differences between proteins within the same family.…”
Section: B Subtle Distinctions Between Proteins Within the Same Familymentioning
confidence: 99%
See 2 more Smart Citations
“…Zhou et al . 24 proposed a Context-Free Encoding Scheme (CFreeEnS) prediction method that allows to be integrated with a large number of different substitution matrices for protein sequences.…”
Section: Introductionmentioning
confidence: 99%